Photon emission and current-collapse suppression of AlGaN/GaN field-effect transistors with photonic–ohmic drain at high temperatures. (13th June 2018) - Tang, Xi; Zhang, Zhaofu; Wei, Jin; Li, Baikui; Wang, Jiannong; Chen, Kevin J.
Abstract: The high-temperature performances of AlGaN/GaN photonic–ohmic drain field-effect transistors (PODFETs) were evaluated by investigating the photon-emission behaviors of the photonic drain (P-D) and the dynamic characteristics at various temperatures. The P-D exhibited a robust photon-emission capability at high operating temperatures. Dynamic high-speed hard-switching tests revealed the effectiveness of the P-D and its photon-pumping functionality at deep electron traps to suppress the current collapse for AlGaN/GaN power transistors from room temperature to 200 °C. The results indicate the potential of AlGaN/GaN PODFETs for high-temperature power-switching applications.